Analisis Implementasi Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) dalam Meningkatkan Efisiensi Pengelolaan Keuangan pada Kantor Perwakilan Badan Pengawasan Keuangan dan Pembangunan (BPKP) Provinsi Bali - Sang Ayu Diah Kartika Devi; I Putu Fery Karyada; I Made Endra Lesmana Putra (UNHI Press, 2026)
This study examines the implementation of the Institutional Level Financial Application System (Sistem Aplikasi Keuangan Tingkat Instansi/SAKTI) in improving the efficiency of government financial management. The study was conducted at the Representative Office of the Financial and Development Supervisory Agency (BPKP) of Bali Province using a qualitative case study approach. Data were collected through in-depth interviews, observation, and documentation, and analyzed using data reduction, data display, and conclusion drawing with triangulation to ensure validity. The results show that SAKTI enhances the integration of financial processes, improves data accuracy, and accelerates financial reporting. The system also increases work efficiency by reducing manual administrative tasks and simplifying reconciliation processes. However, challenges remain, including technical disruptions, limited user competence, and coordination constraints. Overall, SAKTI contributes to more efficient, integrated, and accountable financial management, although further improvements are required to optimize its implementation.